PENERAPAN SISTEM PEMERIKSAAN DAN PERBAIKAN RETAKAN PADA DINDING DI KELURAHAN PAKINTELAN KECAMATAN GUNUNGPATI KOTA SEMARANG - Kusumastuti, Dianita Ratna; Marsudi, Marsudi; Goro, Garup Lambang; Santosa, Stefanus; Supriyo, Supriyo; Rabinah, Aiun Hayatu; Praharseno, Fikri; Abdillah, Rifqi Aulia; Sulaiman, Sriwahyuningsih (Bangun Rekaprima, 2024)
Community service in the form of implementing a system for checking and repairing cracks in walls in Pakintelan Village, Gunungpati District, Semarang City aims to increase residents' knowledge regarding the problem of cracks in walls which are thought to be caused by ground movement. This activity starts from a site survey, equipment preparation, and training carried out with the correct procedures, ensuring the implementation of correct repair methods and according to standards. Based on the results of surveys and interviews with local residents, the cracks in the walls of houses that occurred at the Citra Pesona Pakintelan Housing Complex were caused by ground movements which caused non-uniform structural settlement and vibrations resulting from housing construction behind the service location. The service team and students provide guidance and assistance to stone masons and the surrounding community. There were 6 masons who took part in the training and several members of the local community. The repair method used to repair cracked walls is the stitching method.